The effectiveness of mindfulness-based learning in improving students' motivation and academic achievement in Islamic religious education: A quasi-experimental study - Syifaul Fauziah; Sella Nofriska Sudrimo; Muhammad Satir (STAI Auliaurrasyidin Tembilahan, 2026)
Learning in Islamic Religious Education at the senior high school level is frequently characterized by teacher-centered instructional practices that may limit students’ engagement, learning motivation, and academic achievement. Although mindfulness-based learning has been widely discussed in educational research, empirical evidence regarding its implementation in Islamic Religious Education remains limited, particularly at the senior high school level in Indonesia. Therefore, this study aimed to examine the effectiveness of mindfulness-based learning in improving students’ learning motivation and academic achievement in Islamic Religious Education at SMA GUPPI Salawati, Sorong Regency. This study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of all 33 eleventh-grade students, who were grouped into an experimental class (n = 16) and a control class (n = 17). Data were collected using a learning motivation questionnaire based on the ARCS model and a cognitive achievement test developed according to Bloom’s Taxonomy and analyzed using descriptive statistics and the Mann–Whitney U test. The findings showed that students in the experimental group achieved higher learning motivation (M = 62.94) and learning outcomes (M = 85.63) than students in the control group (M = 33.41; M = 65.29), with statistically significant differences (p < 0.001). The experimental group also demonstrated greater improvement in both variables than the control group. These findings indicate that mindfulness-based learning may serve as an effective instructional approach to support student engagement and improve learning outcomes in Islamic Religious Education.